KEBIJAKAN HUKUM PIDANA DALAM PERLINDUNGAN HUTAN - I Wayan Putu Sucana Aryana (Fakultas Hukum Universitas Ngurah Rai, 2021)
Forests are an environment that must be protected. Forest protection is carried out by establishing laws and regulations and programs made by the government, non-governmental organizations and the community. The rate of forest destruction is something that cannot be avoided, both in the form of forest fires, illegal logging and others. In this study, the criminal law policy in forest protection will be discussed. Regulations on forest protection are regulated in The Law Number 41 of 1999 concerning Forestry and The Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction. These provisions regulate prohibited acts. Criminal liability can be held against people who can be legally responsible.